Taking the Challenge: An Exploratory Study of the Challenge-Based Learning Context in Higher Education Institutions across Three Different Continents - Antoine van den Beemt; Patricia Vázquez-Villegas; Sonia Gómez Puente; Fiona O'Riordan; Clare Gormley; Feng-Kuang Chiang; Chuntao Leng; Patricia Caratozzolo; Genaro Zavala; Jorge Membrillo-Hernández (MDPI AG, 2023)
Teaching by subjects and contents where students passively receive knowledge is increasingly obsolete. Universities are opting for teaching strategies supporting skills development to face the labor, social, environmental, and economic conditions afflicting us. Employers demand increasingly complex skills; universities have identified experiential learning as giving access to real situations and learning by doing. One of the most advanced strategies is Challenge-Based Learning (CBL). Through real problem situations, faculty and students collaborate to solve an established challenge, with or without external stakeholders. This educational advancement has been global and is developing graduates with international skills, which ensures a world-class standard. Here we report a global study carried out in universities from three different continents, and we analyze the implementations of CBL in educational programs through cases in Mexico, The Netherlands, Ireland, and China. Developing skills and competencies is evident, and CBL is a viable way to ensure the success of Higher Education graduates. Obstacles in the transformation of faculty towards CBL are a similar fence in all cases. For CBL, the path needs to be explored, as it is on the frontline of educational developments that can be most helpful for developing a new paradigm in education.